"Citizen Martyrs": The Afghan Fatemiyoun Brigade in Iran. Issue 1 (April 2022) - Schwartz, Kevin L.
Abstract : While much is made of the military capacity of the all-Afghan Fatemiyoun Brigade as an Iranian militia and proxy force in Syria, less attention has been devoted to how its fighters and their experiences have been integrated into Iranian society following deployment. As Afghans of the Fatemiyoun Brigade return to Iran – either as veterans or as bodies of martyrs – they have been incorporated into existing national frameworks of Shiʿi identity and martyrdom. Through the analysis of media reports, funeral processions, and visual iconography, this article demonstrates how state and non-state actors in Iran have used the example of Afghan "shrine defenders" as an occasion to re-invigorate the central importance of state narratives around Shiʿism and national sacrifice. Such practices have elicited new perceptions across government and media of Afghan contributions to the history of the Islamic Republic and have been accompanied by new mobilities and modalities for Afghans in Iranian society. While the experiences of Fatemiyoun fighters are not monolithic, and the reasons for enlisting varied, Afghans affiliated with the brigade are increasingly taking on citizenship characteristics, despite their non-citizenship status. In addition to fighting on behalf of the nation and Shiʿa community, Afghan members and veterans of the Fatemiyoun engage in civic acts of solidarity. Families of fallen fighters receive the financial benefits and cultural status accorded to "martyrs families." Accordingly, the experience of the Fatemiyoun Brigade and its increased visibility in Iranian society raise questions about the future citizenship prospects of Afghans in Iran as well as notions of citizenship in the Islamic Republic more generally.